Understanding the Olympics - Horne, John 1955-; Whannel, Garry (Routledge, 2020)
"How did the Olympics evolve into a multi-national phenomenon? How can the Olympics help us to understand the relationship between sport and society? What will be the impact and legacy of the Olympics after Tokyo in 2020? Understanding the Olympics answers all these questions by exploring the social, cultural, political, historical and economic context of the Games. This thoroughly revised and updated edition discusses recent attempts at future proofing by the International Olympic Committee (IOC) in the face of growing global anti-Olympic activism, the changing geo-political context within which the Olympics take place, and the Olympic histories of the next three cities to host the Games - Tokyo (2020), Paris (2024) and Los Angeles (2028) - as well as the legacy of the London (2012) Olympics. For the first time, this new edition introduces the reader to the emergence of 'other Games' associated with the IOC - the Winter Olympics, the Paralympics, and the Youth Olympics. It also features a full Olympic history timeline, many new photographs, refreshed suggestions for further reading, and revised illustrations. The most up-to-date and authoritative textbook available on the Olympic Games, Understanding the Olympics is essential reading for anybody with an interest in the Olympics or the wider relationship between sport and society"--